Pengaruh Kurikulum Merdeka dan Kinerja Guru Terhadap Hasil Belajar Siswa Sekolah Dasar Negeri Se-Kecamatan Jakabaring - Ika Wulandari; Tri Widayatsih; Pahlawan Pahlawan; Indah Ardianti; Ika Lestari (CV. ULIL ALBAB CORP, 2024)
The aim of this research is to determine and analyze the influence of the Merdeka Curriculum and teacher performance on student learning outcomes at State Elementary Schools in Jakabaring District. The sample in this research was 145 State Elementary School students in Jakabaring District. The data collection method used in this research is a questionnaire with a Likert scale. The results of this research show that the independent curriculum has an influence on the learning outcomes of state elementary school students in Jakabaring District. This is shown by the r value as a correlation coefficient (r) which is 0.847, meaning that it can be interpreted that the independent curriculum variable has a very strong relationship to improving learning outcome variables in Jakabaring District, and R2 is 0.837, which means that the independent curriculum variable is able to explain 83.7% of the learning outcome variables, while the other 16.3% is explained by other factors not explained in this research. Teacher performance has a significant effect on the learning outcomes of public elementary school students in Jakabaring District, this is shown by the r value as a correlation coefficient (r) which is 0.887, meaning that it can be interpreted that the teacher performance variable has a very strong relationship to improving the learning outcome variables of students in Jakabaring District. , and the R2 value is 0.841, which means that the teacher performance variable is able to explain 84.1% of the learning outcome variables, while the other 15.9% is explained by other factors not explained in this research. The independent curriculum and teacher performance have a positive and significant effect on the learning outcomes of public elementary school students in Jakabaring District, this is shown by the r value as a correlation coefficient (r) which is 0.887, meaning that it can be interpreted that the teacher performance variable has a very strong relationship to improving the learning outcome variable. students in Jakabaring District, and the R2 value is 0.841, which means that the teacher performance variable is able to explain 84.1% of the learning outcome variables, while the other 15.9% is explained by other factors not explained in this research. For this reason, it is recommended that the principal be able to protect and set a good example for teachers. Applying a good leadership style will motivate teachers to produce good ways of working too. Teachers are able to express complaints regarding the principal's leadership style and the feedback they receive from the work they have done.